Collaboration : how leaders avoid the traps, create unity, and reap big results - Hansen, Morten T. (Harvard Business Press, 2009)
Many leaders inherently know that in today's competitive environment, companywide collaboration is an imperative for successful strategy execution. Sadly, most cross-unit collaborative efforts end up wasting time, money, and resources. This book shows managers how to get it right through 'disciplined collaboration'. Deciding when to collaborate- and when not to- is the first critical step in disciplined collaboration. To master collaboration is to know when not to do it. Highlighted also are four common collaboration traps that managers must avoid: the 'not-invented-here' syndrome; hoarding; search problems; and transfer issues.